EDUCATIONAL TECHNOLOGIES IN STUDENTS' INDEPENDENT STUDY OF THE SUBJECT "DETERMINATION OF THE PHYSICAL PARAMETERS OF A STAR BASED ON ITS COLOR" - Hotamov, Jaxongir (Физико-технологического образование, 2022)
In this article, the knowledge that students should know about the topic of determining its physical parameters based on the color of a star and the educational technologies of independent understanding of the topic, its methodology and importance are shown